Dragon's Shadow: China's Influence and Erosion of Democracy in Southeast Asia - Thapa, Santa Bahadur (Darul Yasin Al Sys, 2025)
This article explores China’s growing presence in Southeast Asia and aims to look beyond the standard geopolitical mischief to appreciate its nuance. It spotlights “Complex Dependency,” under which Southeast Asian states ride the coattails of China’s rise even as it threatens to corrode democratic norms. A qualitative research approach is followed in the study, and literature review and case studies are dealt with critically and interpretively. Among the key findings, there is evidence that China's economic cooperation, political strategies, and cultural diplomacy influence democratization. Chinese investment, primarily through the Belt and Road Initiative, can drive economic development without democratic or human rights oversight, which may lead to supporting autocratic regimes. The paper submits that this deepening dependence on China, with its characteristic assertiveness, undermines the pattern of delicate regional democracies, subtly hollowing out democracy norms and practices. Maintaining a proper balance between economic benefits and democratic values should be based on a well-informed interpretation of “Complex Dependency”.